Robust Shot Boundary Detection from Video Using Dynamic Texture - Taile, Peng; Wenjun, Zhang (Sensors & transducers, 2014)
Video boundary detection belongs to a basis subject in computer vision. It is more important to video analysis and video understanding. The existing video boundary detection methods always are effective to certain types of video data. These methods have relatively low generalization ability. We present a novel shot boundary detection algorithm based on video dynamic texture. Firstly, the two adjacent frames are read from a given video. We normalize the two frames to get the same size frame. Secondly, we divide these frames into some sub-domain on the same standard. The following thing is to calculate the average gradient direction of sub-domain and form dynamic texture. Finally, the dynamic texture of adjacent frames is compared. We have done some experiments in different types of video data. These experimental results show that our method has high generalization ability. To different type of videos, our algorithm can achieve higher average precision and average recall relative to some algorithms. [PUBLICATION ABSTRACT]